Reticulocyte hemoglobin concentration for screening iron deficiency in very low birth weight preterm neonates - Mallika Pomrop (2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group. Background: Preterm and low birth weight infants are at risk of iron deficiency. Reticulocyte hemoglobin concentration may be useful as a screening test to diagnose iron deficiency in preterm neonates. Objective: To evaluate the accuracy and establish the reticulocyte hemoglobin concentration cutoff value for iron deficiency diagnosis in very low birth weight preterm neonates. Method: This study was conducted between May 2018 and March 2019 at Chiang Mai University Hospital. Preterm infants born at gestational age ≤34 weeks and birth weight ≤1500 g were enrolled. Blood samplings were obtained within the first 48 h of life. Iron deficiency was defined by using two or more of these following parameters: mean corpuscular volume <100 fL, transferrin saturation <16% and serum ferritin <30 µg/L. Neonatal anemia was defined as hemoglobin <15 g/dL. The optimum reticulocyte hemoglobin concentration cutoff values were performed by using predictive values and receiving operation characteristic analysis. Result: Fifty-seven preterm neonates were enrolled. Nine (15.7%) and three (5.3%) neonates had iron deficiency and iron deficiency anemia, respectively. The reticulocyte hemoglobin concentration cutoff value of <29 pg showed the optimum accuracy to diagnose iron deficiency in very low birth weight preterm neonates with sensitivity, specificity, positive and negative predictive values of 89%, 79%, 42% and 97%, respectively. Conclusion: Reticulocyte hemoglobin concentration can be used as a screening parameter to diagnose iron deficiency for VLBW preterm neonates. The optimum cutoff value which provided the acceptable accuracy was <29 pg.